(untitled) (Academicia Globe: Inderscience Research, 2022)
Along with the observations of traditional methods of analysis in linguistics, there is a growing interest in new methods of analysis that connect it with sociology, psychology and other disciplines. New modern trends in linguistics related to these methods of analysis are emerging. One such field is lingvogenderology. The research source of this science is the study of gender features of language, in which two issues are the differences and peculiarities of women’s and men’s speech; the language system focuses on language units that represent concepts related to masculinity and femininity. The article discusses women’s speech and their distinctive features and differences that appear when we contrast them with men’s speech.